Innovative approaches to ethical and methodological challenges in health research - Freitas, C. (European Congress of Qualitative Inquiry, 2018)
Qualitative health research about sensitive topics and/or involving people in a position of vulnerability is prone to raise ethical and methodological challenges: power unbalances may unintendedly expose participants to ethical risks by leading them to perceive an obligation to answer research questions that cause discomfort, or to remain engaged in a study from which they would prefer to opt out; legal constraints to revealing one’s identity may raise questions to the use of research methods that foster participant interaction (e.g. group interviewing); and the sharing of intimate information hinting at compromised well-being on the part of participants complicate boundary setting and pose questions as to when a breach in confidentiality may be considered. These challenges may cause researchers to feel uncertain and concerned about the right way to act, particularly when they arise unexpectedly. Moreover, they may lead participants to feeling compelled to participate in studies that increase their sense of disadvantage and disempowerment. Conversely, they may limit potential participants’ willingness to engage in and keep on participating in scientific studies, causing the circumstances and problems that contribute to their vulnerability to remain unresearched, unknown and unsolved.Ideally, ethical and methodological challenges would be pre-empted. This purpose may be achieved through a combination of ethical imagination and empirically-based research aimed at anticipating and defining strategies to prevent unnecessary challenges to unfold and clearly outlined pathways to deal with those that cannot be averted. However, professional guidance for ethical practice and population-specific guidelines for health research are not always unequivocal and many grey areas subsist as a result. This symposium aims to facilitate discussion about innovative approaches and study designs developed to investigate complex phenomena in the field of health. It will do so by promoting a transdisciplinary dialogue amongst researchers whose empirical studies seek to unpack the ethical dilemmas and methodological challenges associated with conducting health research about sensitive issues and/or with people experiencing vulnerability. The four studies selected encompass a myriad of interrelated research topics including fertility, gamete donation and parenthood. Empirical research on these topics lays the groundwork for discussing: 1) ethical challenges associated with interviewing participants in spaces “loaded” with mixed emotions for both participants and researchers; and, categorising participants who do not necessarily identify with categories defined a priori by researchers; and 2) methodological challenges associated with using elicitation techniques to collect data on moral reasoning; selecting a sampling strategy, techniques for data collection and a topic guide to obtain information about the content adequacy of fertility clinics’ websites; and, controlling for father’s occupation when analysing couple interviews about parenting preterm infants.